Female Empowerment Through Domestic Noir in Gillian Flynn's Gone Girl and A.S.A. Harrison's The Silent Wife - HADAOUİ, HOUCİNE (İstanbul Kültür Üniversitesi, 2025)
This thesis aims to introduce and explain what the domestic noir genre is and whether it should be considered an independent genre or sub-genre of crime fiction. It also examines how this new genre contributes to the literary domain and the way it empowers victims of domestic abuse. Through analysing the two novels Gone Girl by Gillian Flynn and A.S.A. Harrison's The Silent Wife, looking at the reasons women in the novels endured the abuse from their husbands, not being able to leave their abusive husbands and ending up choosing violence and murdering them. It also explores the motive behind the abuse committed by the male characters in the novels, what made them violent and abusive towards their partners and why they were unfaithful in engaging in relations with other women. This thesis has concluded that since its aim distinguishes it from crime fiction in its message and structure, domestic Noir depicts the struggles faced by women subjected to domestic abuse, who end up killing their husbands to save their own lives, unlike crime fiction, which describes a thrilling murder mystery. This thesis also reveals the subtle motivations driving the actions of both male and female characters, attributing them to societal pressures and parental abuse. This genre sheds light on the lives of abused women and their untold stories, concealed behind closed doors, raising awareness on this critical issue and empowering women in a similar circumstance to stand up for themselves, instead of waiting to be rescued.
Keywords: Domestic Noir; Gone Girl; The Silent Wife; Domestic Abuse; Women’s rights; Psychological Analysis; Marital Infidelity; Justifiable Homicide